1960
DOI: 10.1084/jem.112.1.225
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Reduces Incorporation of Radioactive Sulfate Into Cartilage and Aortas of Rats

Abstract: Hormonal influences on connective tissues have been observed for a variety of hormones and a variety of sites. Gonadal hormones cause accumulation of intercellular ground substance in certain locations; the sex skin of monkeys (1) and the cock's comb (2) are well known examples. The metabolism of sulfated mucopolysaccharide components of connective tissue is known to be influenced by growth hormone (3, 4) and adrenal steroids (5, 6, 7), but only cursory metabolic studies have been reported using sex hormones (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1962
1962
1979
1979

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 25 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…First, both estrogens and progestogens have unpredictable effects on blood pressure in normal man and other animals (24,25), which would add another variable to any study of their effects. This variable was avoided in the present study in view of the similar levels of hypertension attained by groups H, E, and P. Second, the difference in growth rate of the estrogentreated animals was anticipated (12). We have previously shown that the degree of changes in the vessel wall induced by hypertension are so striking that they overwhelm any growth-related differences in vessel wall morphology and chemistry (6,20).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…First, both estrogens and progestogens have unpredictable effects on blood pressure in normal man and other animals (24,25), which would add another variable to any study of their effects. This variable was avoided in the present study in view of the similar levels of hypertension attained by groups H, E, and P. Second, the difference in growth rate of the estrogentreated animals was anticipated (12). We have previously shown that the degree of changes in the vessel wall induced by hypertension are so striking that they overwhelm any growth-related differences in vessel wall morphology and chemistry (6,20).…”
Section: Discussionmentioning
confidence: 89%
“…However, the protective effect does not seem to be wholly explainable by the lipid changes induced by estrogen treatment. The role of vessel wall factors in this protection has been postulated (8,12).…”
mentioning
confidence: 99%
“…The effect does not appear to be a direct one since sulfate incorporation by chondrocytes in tissue (6) or cell (9) culture is not diminished by in vitro exposure to estrogens in the media. The observation that the suppressive effect of estrogens on cartilage requires a 3-day latency period of administration (6) suggests that the action of estrogen on cartilage is in- direct. Estrogen inhibition of somatomedin (sulfation factor) could explain these findings.…”
Section: Discussionmentioning
confidence: 94%
“…Silberberg and Silberberg ( 4 3 found that male mice genetically predisposed to a high incidence of osteoarthritis had decreased frequency and severity of lesions with estrogen administration. In vivo and in vitro studies after estradiol administration to animals revealed depressed sulfate metabolism in normal rat hyaline costal cartilage (6) and rabbit epiphyseal cartilage (7). Other in vitro studies in which estrogens were added to cell cultures revealed suppression of chondrocyte proliferation (8) and possible stimulation of 35S0, incorporation by these cells (9).…”
mentioning
confidence: 99%
“…Loss of mucopolysaccharide from the matrix is often considered as an early if not the primary event in the joint disease [5]. Since estrogen inhibits the production of mucopoly saccharide by chondrocytes [6], the hormone should be expected to promote rather than inhibit the evolution of the lesions. Yet, decreased synthesis of mucopolysaccharides might be counterbalanced by in creased polymerization [7] or linking of MPS with collagen.…”
Section: Observationsmentioning
confidence: 99%